New Perturbation Iteration Solutions for Fredholm and Volterra Integral Equations - İhsan Timuçin Dolapçı; Mehmet Şenol; Mehmet Pakdemirli (Journal of Applied Mathematics)
In this paper, recently developed perturbation iteration method is used to solve Fredholm and Volterra integral equations. The study shows that the new method can be applied to both types of integral equations. Some numerical examples are given, and results are compared with other studies to illustrate the efficiency of the method.